Networks in action : business choices and telecommunications decisions - Keen, Peter G. W. (Wadsworth, 1994)
Telecommunications as a business resource. Telecommunications network fundamentals. The telecommunications decision sequence. Terminals and workstations. Transmission links. Transmission methods. Standards and architecture. Types of networks. Networks in action. Choosing the right opportunity...